The Curative Fallacy - Aikin, Scott; Talisse, Robert (Informal Logic, 2026)
The curative fallacy is a unique error in reasoning. It has not yet been identified in fallacy theory, so we propose here an initial statement of how to identify and criticize the error. One commits the fallacy when one reasons that means that would have prevented an unwelcome outcome are also means, after the outcome has come about, for eliminating or mitigating the outcome. That is, one takes prevention to be ipso facto also cure. This reasoning is appropriate under what we call symmetric conditions, where the preventative is also the curative, but it is not appropriate under asymmetric conditions, where the preventative not only does not remediate but can actually make things worse. This fallacy is particularly appealing for political and interpersonal circumstances, and we identify a few examples of it in contemporary intellectual culture.